KONTRIBUSI MINAT DAN MOTIVASI TERHADAP PEMBINAAN PRESTASI SEPAKBOLA - I Wayan Swastika; Surisman Surisman; Wiyono Wiyono (JUPE (Jurnal Penjaskesrek), 2015)
This study aims to determine the contribution of the interest and motivation to football coaching achievements. The method used is survey data by using correlational analysis. The collection of data is in the form of interest, motivation and coaching football achievements using a questionnaire. The sample used was a student of Physical Education amounting to 45 students. The analysis showed that the correlation coefficient of interest to coaching football achievements is 0,559. Correlation coefficient motivation to coaching football achievements is 0.639. While the correlation coefficient the interest and motivation to coaching football achievements is 0.826. This means that interest accounted to 31.2%. Motivation accounted to 40.8%. While interest and motivation give contribution to the achievement of coaching football at 68.2%. The Conclusion of this study shows that the interest and motivation have contributed very "strong" to coaching football achievements of Physical Education.Penelitian ini bertujuan untuk mengetahui kontribusi antara minat dan motivasi terhadap pembinaan prestasi sepakbola. Metode penelitian yang digunakan adalah survei dengan analisis data menggunakan korelasional. Pengumpulan data berupa minat, motivasi dan pembinaan prestasi sepakbola menggunakan angket. Sampel yang digunakan adalah mahasiswa Pendidikan Jasmani yang berjumlah 45 mahasiswa. Hasil analisis menunjukkan bahwa koefesien korelasi minat dengan pembinaan prestasi sepakbola 0,559. Koefesien korelasi motivasi dengan pembinaan prestasi sepakbola 0,639. Sedangkan Koefesien korelasi minat dan motivasi dengan pembinaan prestasi sepakbola 0,826. Artinya minat memberikan kontribusi sebesar 31,2%. Motivasi memberikan kontribusi sebesar 40,8%. Sedangkan minat dan motivasi memberikan kontribusi terhadap pembinaan prestasi sepakbola sebesar 68,2%. Kesimpulan penelitian ini menunjukkan bahwa minat dan motivasi memiliki kontribusi yang sangat kuat terhadap pembinaan prestasi sepakbola Pendidikan JasmaniKata kunci : minat, motivasi, sepakbola.